Interfacial solar‐driven steam and electricity co‐generation using Hydrangea‐like graphene by salt‐assisted carbonization of waste polylactic acid - Huiyue Wang; Xueying Wen; Kuankuan Liu; Qiuxuan Liu; Guixin Hu; Huajian Liu; Yan She; Ran Niu; Tao Tang; Jiang Gong (SusMat)
Abstract The interfacial solar steam generation and water evaporation–driven power generation are regarded as promising strategies to address energy crisis. However, it remains challenging to construct low‐cost evaporators for freshwater and electricity co‐generation. Herein, we report a salt‐assisted carbonization strategy of waste polylactic acid to prepare Hydrangea flower–like graphene and build a bi‐functional graphene‐based evaporator. The evaporator presents merits of good sunlight absorption, photo‐to‐thermal conversion property, water transport, good thermal management capability, and negatively charged pores for the continuous diffusion of ions. Hence, it achieves the evaporation rate of 3.0 kg m−2 h−1 and output voltage of 0.425 V, surpassing many advanced evaporators/generators. Molecular dynamics simulation result proves that more Na+ ions are attracted by functional groups, especially –COOH/C–OH, to promote Na+ selectivity in nanochannels. This work offers new opportunities to construct multifunctional evaporators for freshwater and electricity co‐generation.